TATA RUANG DAN AMBISI PEMEKARAN KABUPATEN INDRAMAYU: TINJAUAN HIERARKI CHRISTALLER - Anth Meylisa Hardadi; Adia Alilatulbariza; Ayu Nuraeni; Selsya Nesha Beiher Lumentut; Sri Aulia (Jurnal Geografi, 2026)
This research evaluates the ineffectiveness of the spatial hierarchy in Indramayu Regency, which triggers development disparities between the central and western regions. Applying Walter Christaller's Central Place Theory, this qualitative descriptive study examines the rationality behind the demand for the establishment of the West Indramayu New Autonomous Region (DOB). Data were gathered through field observations, in-depth interviews, and secondary sources, and then analyzed using the Central Place Theory and the evaluation of regional expansion feasibility parameters. The findings indicate a functional failure in the maximum range of the parent city's service center; residents in the western region must travel 70 km (taking 1.5–3 hours) to access high-order services. This spatial barrier triggers a leakage in public mobility orientation toward Subang Regency. Theoretically, the proposed West Indramayu New Autonomous Region has exceeded the required threshold, supported by a demographic base of over 700,000 inhabitants and a high centrality index in Kroya District as the prospective capital. This study concludes that regional expansion in West Indramayu is not merely a political commodity, but rather a logical spatial necessity.